The effects of misuse personal devices in workplace towards employee productivity: a study on National University of Malaysia (UKM) / Abdul Hakim Ab Razak - Ab Razak, Abdul Hakim (Faculty of Business and Management, 2014)
In this topic researcher will be discussing on the background of the study, problem statement, research objective, research question, theoretical framework, hypothesis, scope of study, significant of study, limitation of study and definition of term. This research is focused on the effects of misuse personal devices in National University Malaysia (UKM) Bangi. In the background of the study, it will focus on dependent and independent variables. In this research, the dependent variable is UKM Bangi employee productivity. While distraction by personal devices and electronic harassment is the independent variables for this research. Problem is defined as an issue occurs that are need to be investigated. For the problem statement, researcher focus about the problem occur in most office that affect the level of employee’s productivity. After further study, researcher able to develop a theoretical framework, from that the hypothesis is gain and help to show the relationship between the variables. From this research, the research questions are being determined that show relationships to the theoretical framework. Then, researcher also discuss the research objectives. It is important because it was review the relationship between the research question and research objective. Based on all topics that researcher has discuss in chapter one, researcher able to identify effects of using personal devices in workplace towards the productivity of UKM employees. It also gives additional information needed to both parties either for the management and the employee.